Pendampingan Penerapan Sistem Manajemen Keselamatan Konstruksi (SMKK) dan Manajemen Traffic Control pada Pekerjaan Rekonstruksi Jalan Jalur Padat Perkotaan - Arqam Laya; Satar Saman; Muhammad Rizal Mahanggi; Berni Idji; Anton Kaharu (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Road reconstruction works in dense urban corridors, such as the Brigjen Piola Isa CS segment passing through health and educational facility zones, pose high risks of traffic congestion and occupational accidents. This community service project aimed to provide technical assistance for implementing the Construction Safety Management System (SMKK) and traffic control management to the executing contractor partner (PT. Tri Sandi Yudha) and local traffic wardens. The implementation method comprised interactive socialization, safety equipment training, and direct field assistance for traffic zone arrangements.  The results showed an increase in worker awareness and compliance regarding the consistent use of standard Personal Protective Equipment (PPE), including safety helmets, safety shoes, and reflective vests. The provision of fire extinguishers (APAR) and temporary safety signs was also successfully integrated into the work area. In terms of traffic management, the structured deployment of traffic cones and warning light sticks effectively mitigated potential traffic congestion and minimized accident risks for road users in active urban corridors. This assistance program successfully established a safe, orderly, and security-compliant construction workspace.